2022
DOI: 10.3390/su14084720
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Transformational Leadership in Building the Resilience of Local Governance Networks

Abstract: Resilience has become more popular among researchers and practitioners of public governance. Previous studies indicate the importance of social capital and leadership in this research field, but mainly theoretically and rarely are considered together. Therefore, this article aims to analyze the impact of social capital and transformational leadership on the resilience of local governance networks based on a questionnaire conducted among 199 local governments in Poland. The variance-based structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…Our result of H1 agrees with the results of Pawłowska (2018) ; Chowdhury et al (2019) ; Jia et al (2020) ; Sienkiewicz-Małyjurek (2022) who found that networks and resources enterprises can access through their RC help them develop organizational resilience. More importantly, as RC appears to be important for survival amidst crisis times, we conducted our study amidst the period of COVID-19 proved the significance of having strong relationships and networks with business partners to support OR.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our result of H1 agrees with the results of Pawłowska (2018) ; Chowdhury et al (2019) ; Jia et al (2020) ; Sienkiewicz-Małyjurek (2022) who found that networks and resources enterprises can access through their RC help them develop organizational resilience. More importantly, as RC appears to be important for survival amidst crisis times, we conducted our study amidst the period of COVID-19 proved the significance of having strong relationships and networks with business partners to support OR.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…These ties inherent in RC connect different groups, allowing information flow among them, and generating more opportunities to deal with difficult circumstances. Therefore, in light of our results, we can conclude that RC could enhance the building of OR through utilizing and strengthening existing links, mutual transformation, and the generation of common situational perception ( Sienkiewicz-Małyjurek, 2022 ).…”
Section: Conclusion and Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The discourse on decentralised climate governance in the Global South in general and Africa in particular has gained momentum over the past few decades. As part of its first climate strategy, the African Union encouraged member states to decentralise climate governance to local governments (Muesiri & Ojong, 2018;Sidik, 2022;Sakapaji, 2021;Sienkiewicz-Małyjurek, 2022). However, like many regions in the Global South, the need to decentralise climate governance in Africa is likely to be affected by several factors.…”
Section: Introductionmentioning
confidence: 99%